Microstructure and mechanical properties of TiNbFeCoAl alloys prepared by semi-solid sintering assisted by thermo-mechanical field. (August 2021) - Kang, L.M.; Pang, X.; Tan, H.G.; Qiu, Y.F.; Liu, H.L.; Luo, X.C.; Li, Z.J.; Yang, C.
Abstract: In this study, the semi-solid sintering of TiNbFeCoAl amorphous powder was carried out by hot isostatic pressing (HIP) and spark plasma sintering (SPS), both of which are assisted by thermo-mechanical field, and finally two alloys with eutectic structure were prepared. The results show that the SPSed and HIPed alloys are composed of hypoeutectic (local ultra-fine lamellar eutectic β-Ti + TiFe and residual spherical β-Ti) and equiaxed Ti2 Co phase. However, the size of hypoeutectic structure in SPSed alloy is about one third of that in HIPed alloy, and the size of the Ti2 Co phase is not much different. Moreover, the Ti2 Co phase in SPSed alloy is uniformly dispersed, while that in HIPed alloy is more likely to gather at the β-Ti grain boundaries. In addition, compared with the HIPed alloy, there is an obvious orientation relationship between the eutectic lamellae of SPSed alloy, which exhibits higher yield strength (1580 ± 6 MPa) and larger plastic strain (26.2 ± 0.6%). The failure analysis shows that eutectic structure can effectively prevent the propagation of micro cracks and mainly contribute to the yield strength of the alloys, while the stable phase boundaries, spherical β-Ti and dispersed Ti2 Co particles mainly contribute to the strength and plasticity of the alloy. Highlights: Semi-solid sintering of TiNbFeCoAl amorphous powder was carried out by SPS and HIP. Both alloys are microscopically composed of Ti2 Co phase and hypoeutectic TiFe+β-Ti. The hypoeutectic structure in the SPSed alloy is finer than that in the HIPed alloy. The SPSed alloy shows better yield strength of 1580 MPa and plastic strain of 26.2%. Eutectic lamellae with stable interfaces mainly promote yield strength of alloys.